Diagnóstico energético del sistema de reinyección de agua de formación en el campo villano “a” de la empresa Agip Oil en la provincia de Pastaza en el año 2013. Propuesta de una metodología para evaluación energética en el sistema de reinyección con aeroenfriadores - Salazar Espín, Miguel Ángel (2017)
Injection water within the Oil Industry has assumed greater attention in its treatment and optimization because it constitutes a very important energy transportation within the cost of producing one barrel of oil, its treatment improves the quality of injection and its proper handling establishes improvements in energy consumption. The energy consumption will depend on the efficiency of the surface equipment that is directly related to the temperature of the reinjection water, the characterization of the variables immersed in the process allows an evaluation to be carried out before and after the implementation of the cooling system with Aero-coolers highlighting the most convenient to reduce energy consumption. It is associated to the cooling of the water of reinjection the phenomenon of Thermal broken that affects positively for the increase of the reinjection. The research project identifies important variables such as pressure, temperature, flows directly after the temperature change of the reinjection water, which will allow us to perform an evaluation in the operation of water injection pumps because they represent the highest energy consumption. Decreasing the temperature substantially improves its performance, which decreases energy consumption. A type of evaluation methodology is proposed according to the system that will allow us to maintain a control in the air coolers as in the surface equipment, trying to ensure that the incidence of the high temperature of the reinjection water affects the Water Injection of Training and energy consumption.